Efficacy, Safety, and Cost-Effectiveness Analysis of Ceftazidime-Avibactam versus Polymyxin B in the Treatment of Carbapenem-Resistant Enterobacteriaceae Infections: A Target Trial Emulation - Na Hu; Fengjiao Xiao; Yechao Chen; Qiaoling Gu; Pei Liang; Yin Xu; Jinchun Liu; Yunxing Liu; Yi-chen Li; Yinqiu Xu; Mengyin Liu; Dayu Chen; et al. (Infectious Diseases and Therapy)
Abstract Introduction Treatment options for carbapenem-resistant Enterobacteriaceae (CRE) infections are limited, with polymyxin B (PMB) and ceftazidime-avibactam (CZA) being among the available choices. However, research on these options is scarce and significantly heterogeneous. This study aims to analyze the efficacy, safety, and cost-effectiveness of PMB and CZA within a standardized target trial emulation (TTE) framework. Methods This retrospective study emulated a target trial to evaluate the efficacy, safety, and cost-effectiveness of CZA versus PMB for treating CRE infections. Conducted at Nanjing Drum Tower Hospital, this study included adult patients treated with CZA or PMB from July 2020 to December 2022. Data on demographics, treatment outcomes, and costs were collected. The primary outcomes included clinical cure, incidence of adverse drug reactions (ADRs), and cost-effectiveness. Secondary outcomes assessed 28-day all-cause mortality, microbiological eradication rates, incidence of acute kidney injury (AKI), and gastrointestinal events. The outcomes were assessed using the modified intention-to-treat (mITT) effects, per-protocol effects, and propensity score overlap weighting (PSOW) methods. Results Between July 1, 2020, and December 31, 2022, 492 hospitalized patients treated with CZA or PMB were screened at Nanjing Drum Tower Hospital. Following inclusion and exclusion criteria, 176 patients were included in the mITT analysis, and 153 in the per-protocol analysis. The clinical cure rate was significantly higher in the CZA group compared to the PMB group across all analyses. The 28-day mortality was similar between groups, while the microbial eradication rate was significantly higher in the CZA group compared to the PMB group across all analyses. The incidence of ADRs was consistent between groups, but AKI occurred more frequently in PMB patients, while gastrointestinal events were more common in the CZA group. The CZA strategy demonstrated a 28.1% increase in efficacy, with an incremental cost-effectiveness ratio of 71,651.76 yuan. Sensitivity analyses confirmed the robustness of these findings. Conclusions This study demonstrates that CZA has a higher clinical cure rate compared to PMB within a standard TTE framework. However, the overall incidence of ADRs was similar between the two treatments. Pharmacoeconomic analysis also indicated that CZA is cost-effective. Trial registration https://www.chictr.org.cn ; identifier, ChiCTR2300067946.